BASELINE STUDIES OF THE CLAY MINERALS SOCIETY SOURCE CLAYS: SPECIFIC SURFACE AREA BY THE BRUNAUER EMMETT TELLER (BET) METHOD - Dogan A.U.; Dogan M.; Onal M.; Sarikaya Yu.; Aburub A.; Wurster D.E. (My University, 2006)
Specific surface area measurements of The Clay Minerals Society source clays were made by the Brunauer, Emmett and Teller (BET) method of adsorption of nitrogen gas. Two replicate measurements of specific surface area were performed for each source clay. All pair values were within 3%, which is very good agreement for this type of measurement.
Keywords: BET; HECTORITE; KAOLINITE; MONTMORILLONITE; PALYGORSKITE; SOURCE CLAYS; SPECIFIC SURFACE AREA